2018
DOI: 10.1134/s2079970518010045
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of R&D, Knowledge Spillovers, and Dynamics of the Economic Growth of Russian Regions

Abstract: The article explores the interrelations between research and development (R&D), innovation activity, and economic growth in the Russian regions. To analyze these interrelations, the econometric framework is applied. Based on data for 2005-2013, panel regression with fixed effects and the Arellano-Bond model are constructed. Hypotheses about the significant impact of knowledge and socioeconomic conditions on regional growth have been tested, while the expenditure on R&D and technological innovation are used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The authors applied the haversine formula to measure distances between regions. A 2005–2013 study of Russian regions confirmed a positive effect of knowledge spillovers (in the form of expenditure on R&D and on TI in fixed‐effects models), while the spillovers did not affect growth in GMM estimations (Kaneva & Untura, ). Lobodina and Schmidt () evaluated knowledge spillovers between Eastern and Western regions of Russia using the knowledge production function, econometric models, and Moran's index.…”
Section: Main Hypotheses Of the Studymentioning
confidence: 92%
See 2 more Smart Citations
“…The authors applied the haversine formula to measure distances between regions. A 2005–2013 study of Russian regions confirmed a positive effect of knowledge spillovers (in the form of expenditure on R&D and on TI in fixed‐effects models), while the spillovers did not affect growth in GMM estimations (Kaneva & Untura, ). Lobodina and Schmidt () evaluated knowledge spillovers between Eastern and Western regions of Russia using the knowledge production function, econometric models, and Moran's index.…”
Section: Main Hypotheses Of the Studymentioning
confidence: 92%
“…The particular combination of positive and negative factors in the organization of science and innovation in Russia after the 1990s has led to a situation in which R&D and knowledge flows now are no longer straightforward or easily interpreted, thus making the task of econometric modeling of the effect of R&D and innovation growth challenging for the authors. This difficulty was further exacerbated by the low number of studies that quantify the impact of regional R&D expenditure on economic growth (see Lobodina & Schmidt, ; Aldieri et al, ; Kaneva & Untura, ). The current paper addresses this gap in the literature.…”
Section: Russia and Characteristics Of Its Innovative Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If to speak about the present, then there is such situation at which at the macro level economic indicators is more or less obvious and are more studied, but the analysis of factors and systematization of approaches to studying of development of regions of Russia remains logically not ended (Kaneva & Untura, 2018).…”
Section: Introductionmentioning
confidence: 99%